Proceedings of the 10th International Conference on Fracture Mechanics of Concrete and Concrete Structures 2019
DOI: 10.21012/fc10.235356
|View full text |Cite
|
Sign up to set email alerts
|

3D printed capsules for self-healing concrete applications

Abstract: This study focuses on the use of additive manufacturing techniques as a possible way to produce novel types of macro-capsules, suitable to be filled with different healing agents and subsequently embedded in cementitious materials to introduce self-healing properties and deal with the sensitivity of these materials to crack formation. Specifically, tubular macro-capsules were produced by 3D printing and filled either with an expansive polyurethane resin or with a liquid sodium silicate. The 3D-printed capsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
“…It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place. Additionally, tubular macrocapsules prepared by extrusion and 3D-printing usually present issues of waterproofing (Anglani et al 2019(Anglani et al , 2020a. According to the procedure followed in these methods, the containers are initially prepared, filled with a liquid healing agent, and subsequently sealed, creating weak points between the interfaces of the containers and the lids.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
“…Studies on capsule-based self-healing utilizing 3D printing technology are relatively limited. Anglani [33] used FDM to print tubular capsules for self-healing concrete using different base materials: PMMA (Polymethyl methacrylate), PLA, PETG (Polyethylene terephthalate glycol-modified), and PET (Polyethylene terephthalate). In case of self-healing capsules, it could be beneficial to use different materials for two reasons: first, the long term stability of the capsule in contact with highly alkaline cementitious medium, as well as with the (internally stored) healing agent must be ensured; and second, the capsule must rupture upon cracking of the concrete to release the healing agent, which needs to be considered during capsule design depending on the base material [34].…”
Section: Self-healing Concretementioning
confidence: 99%
“…In case of self-healing capsules, it could be beneficial to use different materials for two reasons: first, the long term stability of the capsule in contact with highly alkaline cementitious medium, as well as with the (internally stored) healing agent must be ensured; and second, the capsule must rupture upon cracking of the concrete to release the healing agent, which needs to be considered during capsule design depending on the base material [34]. In addition to using different base materials, Anglani et al [33] also used techniques for improving the bond between the capsules and the matrix, for example by coating the capsules with epoxy and sand to increase the surface roughness. This study showed a proof of concept, and the results show a good potential of the proposed capsulebased system for structural applications.…”
Section: Self-healing Concretementioning
confidence: 99%
“…To achieve these roles, the capsules should be designed with sufficient strength to survive the concrete mixing and weak enough to ensure the cracks propagate through the capsules and release the healing agents. To date, glass [ 35 , 36 , 37 , 38 , 39 , 40 ], ceramic [ 41 ], expansive clays [ 34 , 42 ], natural fibers [ 43 , 44 ], perspex [ 38 ], paraffin [ 45 , 46 ], wax [ 47 ], silica [ 48 , 49 ], silica gel [ 50 ], diatomaceous earth [ 51 ], urea-formaldehyde [ 52 , 53 , 54 , 55 ] polymethyl methacrylate [ 54 , 55 ], low alkali cementitious materials [ 56 ], recycled brick aggregates [ 57 ], biocapsules (made of carbide slag fly ash and desulfurized gypsum) [ 58 ], sugar-coated expanded perlite [ 59 ] and porous concrete [ 60 ] have been investigated as capsule shell materials. In polymeric microcapsules, urea-formaldehyde, polyurethane, and melamine-formaldehyde are amongst the most commonly used polymeric encapsulation materials [ 61 ].…”
Section: Introductionmentioning
confidence: 99%